Management of time and communication among selected Filipino housewives - Pangilinan, Ma Cecilia Laxa.; Ronquillo, Carolyn Victoria U. (2005)
This exploratory case study was conducted to describe the management of time and communication of selected Filipino housewives living in Metro Manila, Philippines. The Unified MORES Guidelines for the Socio-Economic Classification of Households was used to determine the social class status of ten respondents. The respondents in this study are five wives belonging to the AB class and five wives from the C class residing in Metro Manila, Philippines. They were each interviewed by the researcher using a questionnaire designed by the researcher. The questions were based on issues relevant to their managing their homes. Only two out of the ten wives are fully employed. The rest are full-time homemakers. All home managers from both classes with the exception of one primarily look after the physical needs of their family. All homemakers employed paid househelpers. The two full-time working mothers from the AB class were structures with their use of time and manner of communicating tasks primarily to their helpers. The remaining eight full-time homemakers followed a loosely structured time management system. They commonly addressed conflicts that arose from relationships with their family members most especially their spouse. The two working mothers from the AB class said that their conflicts arose from the management of their maids. The study revealed that there were several factors that affect how a wife manages her resources such as time and communication at home. These factors included: the wife's socio-economic status, her educational background and that her husband's, the wife's occupation and that of her husband's as well, the number and ages of her children and the ages, number, years of service and efficiency of her hired household helpers.
October 2005."
Thesis (M. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Housewives -- Time management -- Philippines; Communication in families -- Philippines -- Manila Metropolitan Area; Home economics -- Philippines